Detection of drug misuse--an addictive challenge. Issue 10 (1st October 1999) - Galloway, J H; Marsh, I D
Abstract : It is now accepted that drug misuse is a large and growing problem in the United Kingdom, some estimates of the number of regular illicit drug users being as high as three million. The aim of this paper is to provide insight into the methods used to detect drug misuse. The strategy adopted by one laboratory is described and methods of screening for, and identification of, a wide range of compounds are provided. No claim is made that this is the best approach or that the list of drugs detected is comprehensive; the range of drugs encountered is always increasing and the lists are constantly updated. It is hoped that users of toxicology laboratory services will gain an appreciation of the capabilities and limitations of the techniques available; and that those who may wish to provide such a service will find the necessary information in a readily accessible format.